Analytical modeling of reinforced concrete panel elements under reversed cyclic loadings - Uluğtekin, Denizhan. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
A novel constitutive model – named as the Fixed Strut Angle Model (FSAM) – is proposed in this study for simulating the cyclic shear behavior of reinforced concrete panel elements. The constitution of the FSAM is based on interpretation of previously-developed reinforced concrete panel models, as well as the results of panel tests available in the literature. The FSAM, with its assumptions and limitations clearly stated; is capable of predicting the nonlinear shear behavior and axial-shear response coupling of reinforced concrete panels subjected to generalized and reversed cyclic loading conditions in plane. The main inherent assumption underlying the formulation of the FSAM is that upon cracking of concrete in a reinforced concrete panel, principal stress directions in concrete do not rotate and coincide with fixed crack directions, implying zero shear stresses along cracks and therefore zero shear aggregate interlock. Although this type of behavior have been consistently observed in panel tests, a modeling methodology which assumes fixed principal stress directions for concrete has not been proposed to this date. State-of-the art constitutive material relationships were implemented in the formulation of the proposed model and a nonlinear analysis solution strategy was used for conducting nonlinear quasi-static analyses using the model. Correlation studies were conducted to compare the model predictions with results of cyclic reinforced concrete panel tests available in the literature. The model was shown to capture, with reasonable accuracy, overall behavioral attributes of RC panels, including cyclic shear stress versus shear strain behavior, shear stress capacity, stiffness, cyclic stiffness degradation, pinching, ductility, and failure mode. The model has also yielded promising results on local deformation predictions. The proposed constitutive model is expected to be a feasible candidate for implementation into a two-dimensional finite-element analysis formulation, for efficient and practical response prediction of reinforced concrete walls with various geometries and reinforcement details.
Keywords: Reinforced concrete.